UVEITIS AFTER THE BNT162b2 mRNA VACCINATION AGAINST SARS-CoV-2 INFECTION: A Possible Association. Issue 12 (December 2021) - Rabinovitch, Tamar; Ben-Arie-Weintrob, Yael; Hareuveni-Blum, Tamar; Shaer, Boaz; Vishnevskia-Dai, Vicktoria; Shulman, Shiri; Newman, Hadas; Biadsy, Muhammad; Masarwa, Dua; Fischer, Naomi; Yovel, Oren; Goldfeather-Ben Zaken, Shalhevet; et al.
Abstract : Purpose: To describe uveitis cases after the BNT162b2 mRNA SARS-CoV-2 vaccination. Methods: This is a multicenter, retrospective study. Vaccine-related uveitis diagnosis was supported by the classification of the World Health Organization Adverse Drug Terminology and the Naranjo criteria. Results: Twenty-one patients (23 eyes) with a mean age of 51.3 years (23–78 years) were included. Eight of the 21 patients had a known history of uveitis. The median time from previous to current attack was 1 year (0.5–15 years). There were 21 anterior uveitis cases, two with bilateral inflammation. Eight cases occurred after the first vaccination and 13 after the second vaccination. All but three presented as mild to moderate disease. Two patients developed multiple evanescent white dot syndrome after the second vaccination. The mean time from vaccination to uveitis onset was 7.5 ± 7.3 days (1–30 days). At final follow-up, complete resolution was achieved in all but two eyes, which showed significant improvement. One case of severe anterior uveitis developed vitritis and macular edema after the second vaccination, which completely resolved after an intravitreal dexamethasone injection. Conclusion: Uveitis may develop after the administration of the BNT162b2 mRNA vaccine. The most common complication was mild to moderate anterior uveitis, while multiple evanescent white dot syndrome can also occur less frequently. Abstract : This is the first multicenter report on uveitis after the BNT162b2 mRNA SARS-CoV-2 vaccination. This retrospective study conducted in Israel showed that uveitis after the BNT162b2 vaccination is rare. Most patients presented with anterior uveitis. Two patients developed multiple evanescent white dot syndrome. The uveitis was self-limited in all subjects.